UPAYA PENANGANAN TRAUMA PELECEHAN SEKSUAL MASA LALU - Kasenda, Rinna Yuanita; Takapipi, Costanli; Meta, Joan; Suryani, Suryani; Aruperes, Vamela; Tarigan, Yusmiar Br (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Sexual harassment of children is a problem that often arises in society so that it is difficult to solve and seriously threatens the lives of children or families, apart from damaging the morale of the younger generation who will later become the nation's successors, of course sexual abuse of children is a very heinous act because it will have an impact both psychologically and physique.